Conjugation of Amisulpride, an Anti-Psychotic Agent, with 5-Aminosalicylic Acid via an Azo Bond Yields an Orally Active Mutual Prodrug against Rat Colitis - Wooseong Kim; Dayoon Kim; Seongkeun Jeong; Sanghyun Ju; Hanju Lee; Soojin Kim; Jin-Wook Yoo; In-Soo Yoon; Yunjin Jung (MDPI AG, 2019)
Amisulpride (ASP), an anti-psychotic agent, is a pharmacologically equivalent to sulpiride (SP). Because SP demonstrates anti-ulcer and anti-colitic activities, ASP with an aniline moiety was azo-coupled to salicylic acid to generate 5-(aminoethanoylsulfamoyl)-N-[(1-ethylpyrrolidin-2-yl)methyl]-2-methoxybenzamide (ASP-azo-ASA), with the expectation that it would act as a colon-specific mutual prodrug against colitis. Following a 24 h incubation, approximately 80% of ASP-azo-ASA was cleaved to form ASP and 5-aminosalicylic acid (5-ASA) in the cecal contents, whereas it remained stable in the small intestinal contents. Oral gavage of ASP-azo-ASA (oral ASP-azo-ASA) delivered 5-ASA to the cecum to levels comparable with those observed for sulfasalazine (SSZ; clinical colon-specific prodrug of 5-ASA) and without detectable concentrations of ASP in the blood, indicating efficient colonic delivery. Oral ASP-azo-ASA ameliorated 2, 4-dinitrobenzenesulfonic acid hydrate (DNBS)-induced colitis in rats more effectively than oral SSZ. Additionally, oral ASP-azo-ASA lowered the levels of inflammatory mediators in the inflamed distal colon more effectively than oral SSZ. Combined treatment with 5-ASA and ASP via the rectal route more effectively reversed colonic damage and inflammation than treatment with 5-ASA or ASP alone, confirming the mutual anti-colitic actions of 5-ASA and ASP. In conclusion, ASP-azo-ASA is an orally active mutual prodrug against rat colitis with limited systemic absorption of ASP.